TEMPORAL DEIXIS IN ITALIAN: FUNCTIONAL AND COGNITIVE ASPECTS IN DISCOURSE ORGANIZATION - M. I. Kamolova; A. F. Shamakhmudova (Modern American Journals, 2025)
This article analyzes temporal deixis in Italian from functional and cognitive perspectives. The study focuses on the role of temporal deictic expressions in organizing discourse and creating temporal reference points in communication. The research examines various types of temporal markers in Italian, including adverbs, verb tenses, and temporal conjunctions, analyzing their pragmatic functions in different communicative contexts. Special attention is given to the cognitive mechanisms underlying temporal deixis and its influence on the perception of temporal relationships in Italian discourse. The work demonstrates how temporal deictic elements contribute to discourse coherence and facilitate successful communication between interlocutors.
Keywords: Temporal deixis, Italian language, discourse organization, temporal reference, pragmatics, cognitive linguistics, communication, verb tenses, temporal adverbs, discourse coherence.